Laundering of Proceeds Forest Destruction and Narcotics Crimes: A Resolution of The Conflict Norms - Yanuar, Muh. Afdal (Jurnal Mulawarman Law Review, 2023)
This paper will explain about the conflict of norms that arise because there are 2 (two) similar provisions (offenses) in different laws, related to 'laundering of proceeds of the forest destruction crime ' and 'laundering of proceeds of narcotics crime'. Furthermore, it is also discussed which principles must be applied to resolve the conflict of norms, and which provisions (offenses) must be applied in that case. This paper uses a normative research with a conceptual approach, statutory approach, and case approach. Through this paper it is also concluded that in case of a conflict of norms between special norms and other special norms, the most relevant principle to be applied is the juridische/systematische specialiteit principle, and in the context of the conflict of norms that occurred in case of 'laundering of proceeds of the forest destruction crime ' and 'laundering of proceeds of narcotics crime', the more relevant provision (offense) applied is the 'Money Laundering Offense' as regulated in the Money Laundering Law.